Changes in phenotypic heterogeneity as an adaptation of fungi to environmental stress - Foster, David S. (2019)
Phenotype may vary between genetically identical cells or organisms, despite exposure to an identical environment. This phenomenon is termed phenotypic heterogeneity. The extent of heterogeneity in a particular phenotype may be determined by stochastic or deterministic (including epigenetics) differences arising between cells which may produce cell-to-cell differences, for example in gene expression. The degree of phenotypic heterogeneity associated with a clonal cell population can be determined by its genotype, e.g. specific gene-promoter sequences producing nosier gene expression. A number of single-cell characteristics displaying phenotypic heterogeneity have been identified as fitness-determining. Therefore, heterogeneity is likely to have a bearing on population survival under temporally stable or unstable environmental characteristics (including stress). Previous evidence suggests that environmental stress can select for strains with increased levels of heterogeneity in resistance (heteroresistance) to the given stressors.